Resilience Strategies of Star-Rated Hotels in the Soloraya Region in Response to Public Policy Dynamics - Yohanes Martono Widagdo; Wahyu Tri Hastiningsih; Novac Dhellia; Fauzan Nur Alfian Hafiluddin (Centre of Excellence in Tourism Udayana University, 2026)
This study was motivated by the dynamics of public policy that affect the operational stability of star-rated hotels in the Soloraya region. These conditions require organizations to adopt adaptive resilience strategies to ensure business continuity.Therefore, this study aims to examine the organizational resilience strategies of star-rated hotels in the Soloraya region in response to the dynamics of public policy.The approach used is descriptive qualitative, employing in-depth interviews with the Chief Accountants of 20 star-rated hotels that are members of the AMKAH (Perkumpulan Manajer Keuangan & Akuntansi Hotel) Solo Chapter. Data analysis was conducted thematically through data reduction, categorization, and interpretation.The research findings indicate that organizational resilience is built through operational efficiency, workforce flexibility, and the strengthening of relationships with external stakeholders. Strategic innovations such as service digitization and the optimization of direct promotions are key factors in market adaptation. Furthermore, operational harmony is reinforced through participatory communication, collaborative leadership, and organizational learning. These findings confirm that the integration of adaptive, collaborative, and innovative strategies plays a significant role in building organizational resilience in the hotel industry. This study offers practical contributions to crisis management development and enriches research on business resilience in the hospitality sector.